Development and Validation of Food and Nutrition Literacy Assessment Tool for Iranian High-school Graduates and Youth - Ashoori, Marziyeh (Int J Prev Med, 2020)
BACKGROUND: Food and nutrition literacy (FNL) is an emerging concept that emphasizes not only on personal knowledge, but food and nutrition skills about. This study aimed to develop and validate a food and nutrition literacy assessment tool (FNLAT) for youth and high-school graduates in Iran. METHODS: The study protocol included the following steps: First, FNL components for Iranian high-school graduates and youth were identified through literature review and interviews with experts. Delphi method was used in order to achieve consensus about FNL components. Then, the questionnaire items were generated, and its content and face validity were assessed. Construct validity of the questionnaire was evaluated through applying principal component analysis (PCA) and confirmatory factor analyses (CFA) in the next step. Finally, reliability of the FNLAT was assessed by calculating Cronbach's Alpha and evaluating test-retest reliability. RESULTS: A 104-item questionnaire was developed. S-CVI was ≥90 which confirmed content validity of the questionnaire. PCA suggested that it was constructed of 6 factors, one in knowledge domain (food and nutrition knowledge) and five in skill domain (functional skills, interactive skills, advocacy, critical analysis of information, and food label reading skills). On the basis of CFA, the fit indices of the model had acceptable fit and confirmed construct validity of the FNLAT (X(2)/df = 1.58, RMSEA = 0.041; P = 1.00, RMR = 0.034, GFI = 0.79). The values of Cronbach's Alpha and intraclass correlation coefficient (ICC) confirmed internal consistency and time stability of the FNLAT and its subscales. CONCLUSIONS: The developed FNLAT is a valid and reliable tool to assess FNL in Iranian late adolescents and youth.